Humanizing businesses for a better world of work - Shrivastava, Radhika; Jain, Kokil (Emerald Publishing Limited, 2024)
Humanizing Businesses for a Better World of Work provides a strategic perspective on how organizations can transform their structures and practices to accommodate a more humanized, people-first workplace in the face of the fundamental transitions happening in the post-pandemic world. The book delves into several key areas of organizational transformation such as innovative organizational structures, the collaboration between businesses and B-schools, redesigning work models and environments, the impact of global megatrends on the talent economy, rethinking and cultivating brand's personality and values, and the role of organizational leaders in this process. Editors Radhika Shrivastava and Kokil Jain have brought together a diverse group of contributors to explore the concept of humanizing businesses and the role it plays in developing greater strategic resilience to navigate future shocks. This unique approach will be highly valuable for academic researchers in the field of organizational behaviour, human resource management, and strategic management, as well as MBA/Executive Education students and practitioners in these areas.